Angiogenin: biological role, mechanisms of action, and participation in oncogenesis - D. E. Mikhalev; S. N. Korotenko; A. Yu. Lomovskikh; O. D. Baydik (Бюллетень сибирской медицины, 2025)
Angiogenin is a small polypeptide consisting of 123 amino acids involved in the processes of angiogenesis and tumorigenesis. This protein plays an important role in various physiological and pathological processes through the regulation of cell proliferation, survival, migration, invasion, and differentiation.The lecture presents data on angiogenin production and interaction with various proteins, describes mechanisms of its action, and shows its biological role in angiogenesis and oncogenesis. The literature search was carried out in the PubMed, Medline, Elibrary, Scopus, The Cochrane Library, and RSCI search engines.